The secret files of Professor L. Otto Funn : or stop being a slug, open this book, and make your brain happy - Gors, Steven E. Carrington, Matt.; World Book, Inc. (Chicago : World Book, Inc., 2013)
More than half a century ago, a mysterious figure named Professor L. Otto Funn unlocked the secret to making learning fun and exciting. He recorded his observations in confidential files that he kept hidden in his office. Before Professor Funn could publish his work, he disappeared on a research trip to the Bermuda Triangle, and his files went missing. Decades later, they were discovered deep in the archives of renowned educational publisher World Book. Now for the first time, World Book is sharing them with the public. Each of Professor L. Otto Funn's carefully developed activities includes links to videos and other online content to help readers on their quests.
Keywords: Handicraft -- Juvenile literature; Technology in art -- Juvenile literature